The Efficacy of Cupping Therapy Added to Electroacupuncture and Exercise Therapy on Knee Osteoarthritis - Salehi, Shahin; Hassabi, Mohammad; Abedi Yekta, Amir Hossein; Poursaeid Esfahani, Mehrshad; Ganjalikhani, Maryam (Novelty in Biomedicine, 2023)
Background: Electroacupuncture and exercise therapy have been used to treat knee osteoarthritis, but evidence for adding cupping to this treatment is lacking. Therefore, this study aimed to investigate the effect of cupping and acupuncture combined with exercise on knee osteoarthritis. Materials and Methods: This randomized control trial was done on 56 patients with knee osteoarthritis. We had two groups: a control and an intervention group. Both groups received electroacupuncture and exercise therapy programs. The intervention group received cupping after electroacupuncture plus exercise therapy. The Western Ontario and McMaster Universities Index (WOMAC) questionnaire and Visual Analogue Scale (VAS) measured patient outcomes before and after treatment. Results: All patients’ VAS and WOMAC scores decreased in these two groups after treatment. The difference between VAS and WOMAC scores and pain and knee function was significant compared to the intervention group with the control group (p<0.05). The difference in knee stiffness was not significant comparing the intervention group with the control group (p>0.05). Conclusion: Adding cupping therapy following electroacupuncture and exercise therapy significantly decreased pain and improved function.